2003
DOI: 10.1007/s00134-003-2035-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ICU admission and discharge times on mortality in Finland

Abstract: Weekend ICU admissions are associated with increased mortality, and patients in the ICU are at increased risk of dying in evenings and during nighttime. Our findings may have important implications for organization of ICU services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
5
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 9 publications
6
110
5
2
Order By: Relevance
“…80 -82 However, some studies suggest that patients admitted to the ICU during off hours have higher mortality even after adjustment for severity of illness. [83][84][85][86][87] This evidence has led to consideration of continuous ("24/7") intensivist care. At least 4 observational studies report that introduction of 24-hour in-hospital intensivist coverage of the ICU was associated with lower mortality, 88 -90 fewer complications, and reduced hospital length of stay.…”
Section: Twenty-four-hour In-house Intensivist Coveragementioning
confidence: 99%
“…80 -82 However, some studies suggest that patients admitted to the ICU during off hours have higher mortality even after adjustment for severity of illness. [83][84][85][86][87] This evidence has led to consideration of continuous ("24/7") intensivist care. At least 4 observational studies report that introduction of 24-hour in-hospital intensivist coverage of the ICU was associated with lower mortality, 88 -90 fewer complications, and reduced hospital length of stay.…”
Section: Twenty-four-hour In-house Intensivist Coveragementioning
confidence: 99%
“…Uusaro A et al [3] have shown increased mortality of patients admitted in 18 intensive care units during weekends when compared to weekdays in Finland. In the present study, night time admissions were associated with significantly higher mortality.…”
Section: Discussionmentioning
confidence: 98%
“…The exact time after which 'after-hours' or 'out of hours' begins varies across studies from after 16Á00 (Uusaro et al 2003), after 18Á00 or 19Á00 (Harvey et al 2005, Hanane et al 2008 or after 22Á00 (Goldfrad & Rowan 2000). Some also include weekends as after-hours depending on staffing levels at weekends (Laupland et al 2008).…”
Section: Introductionmentioning
confidence: 95%